Hubungan Kemampuan Komunikasi Interpersonal dan Penggunaan Sumber Belajar Digital dengan Motivasi Belajar Siswa pada Mata Pelajaran Ekonomi di SMA Negeri 2 Sukoharjo - Helmiyah Tsabita; Soetarno Joyoatmojo; Almh. Kristiani (Departement of Mathematics Education, 2023)
The purpose of this research is to test 1) the relationship between interpersonal communication skills and students' learning motivation in economics subjects at SMA Negeri 2 Sukoharjo; 2) the relationship between the use of digital learning resources and students' learning motivation in economics subjects at SMA Negeri 2 Sukoharjo; 3) the relationship between interpersonal communication skills and the use of digital learning resources with students' learning motivation in economics subjects at SMA Negeri 2 Sukoharjo. The research method used was quantitative with a population of class X students at SMA Negeri 2 Sukoharjo. The sampling technique used Simple Random Sampling with a sample size of 125 respondents. Data collection uses a questionnaire. The data validity test in this study used the product moment correlation test, while the reliability test used the Cronbach's Alpha method.